Using behavioral skills training with preservice teachers in the university classroom. (16th December 2020) - Kirkpatrick, Marie; Rehfeld, David M.; Akers, Jessica S.; Rivera, Gabby; Sulak, Tracey N.
Abstract: Preservice and novice teachers often identify behavior management as an area of weakness that they attribute to a lack of sufficient instruction during their teacher preparation. Behavioral skills training (BST) is an evidence‐based teaching methodology based on the principles of applied behavior analysis used to teach new skills. This study investigated the use of BST in the university setting to teach undergraduate preservice teachers enrolled in a field‐based special education course to implement a token economy during small group instruction with children. A single‐case research design was used to assess the effectiveness of using BST by evaluating accuracy of implementation before and after BST. Results showed BST was an effective teaching procedure and social validity measures collected from the preservice teachers indicated BST was acceptable to all participants. Limitations and needs for future research are discussed.